Re: Factor question
- To: mathgroup at smc.vnet.net
- Subject: [mg71303] Re: Factor question
- From: "dimitris" <dimmechan at yahoo.com>
- Date: Tue, 14 Nov 2006 05:06:20 -0500 (EST)
- References: <ej7320$iur$1@smc.vnet.net>
More on this subject... See first the following commands. Any comments on the outputs below? sols = x /. Solve[x^2 - 1 == 0] Factor[x^2 - 1, Extension -> sols] sols = x /. Solve[x^3 - 1 == 0] Factor[x^3 - 1, Extension -> sols] sols = x /. Solve[x^4 - 1 == 0] Factor[x^4 - 1, Extension -> sols] sols = x /. Solve[x^5 - 1 == 0] Factor[x^5 - 1, Extension -> sols] sols = x /. Solve[x^6 - 1 == 0] Factor[x^6 - 1, Extension -> sols] sols = x /. Solve[x^7 - 1 == 0] Factor[x^7 - 1, Extension -> sols] sols = x /. Solve[x^8 - 1 == 0] Factor[x^8 - 1, Extension -> sols] sols = x /. Solve[x^9 - 1 == 0] Factor[x^9 - 1, Extension -> sols] sols = x /. Solve[x^10 - 1 == 0] Factor[x^10 - 1, Extension -> sols] sols = x /. Solve[x^11 - 1 == 0] Timing[Factor[x^11 - 1, Extension -> sols]] sols = x /. Solve[x^12 - 1 == 0] Timing[Factor[x^12 - 1, Extension -> sols]] sols = x /. Solve[x^13 - 1 == 0] Timing[Factor[x^13 - 1, Extension -> sols]] Thanks in advance Dimitris dimitris wrote: > Why Factor gives the follwing output below? > > sols = x /. Solve[x^6 - 1 == 0] > {-1, 1, -(-1)^(1/3), (-1)^(1/3), -(-1)^(2/3), (-1)^(2/3)} > > Factor[x^6 - 1, Extension -> %] > (-1 + (-1)^(1/3) - x)*((-1)^(1/3) - x)*(-1 + x)*(1 + x)*(-1 + > (-1)^(1/3) + x)*((-1)^(1/3) + x) > > that is why it writes e.g. (-1 + (-1)^(1/3) instead of (-1)^(2/3) > > Block[{Message}, FullSimplify[(-1)^(2/3) == -1 + (-1)^(1/3)]] > True > > How is possible to get with Factor the output as follows? > > Times @@ Apply[Plus, Solve[x^6 - 1 == 0], 2] > (-1 + x)*(1 + x)*(-(-1)^(1/3) + x)*((-1)^(1/3) + x)*(-(-1)^(2/3) + > x)*((-1)^(2/3) + x) > > or > > Times @@ Apply[Plus, Flatten[Solve[x^6 - 1 == 0], 1], {1}] > (-1 + x)*(1 + x)*(-(-1)^(1/3) + x)*((-1)^(1/3) + x)*(-(-1)^(2/3) + > x)*((-1)^(2/3) + x)] > > Regards > Dimitris